2020
DOI: 10.5334/gh.808
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Spectrum of Cardiac Arrhythmias in Sub-Saharan Africa

Abstract: Major structural cardiovascular diseases are associated with cardiac arrhythmias, but their full spectrum remains unknown in sub-Saharan Africa (SSA), which we addressed in this systematic review. Atrial fibrillation/atrial flutter (AF/AFL) prevalence is 16-22% in heart failure, 10-28% in rheumatic heart disease, 3-7% in cardiology admissions, but <1% in the general population. Use of oral anticoagulation is heterogenous (9-79%) across SSA. The epidemiology of sudden cardiac arrest/death is less characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 127 publications
3
30
0
4
Order By: Relevance
“…L´HTA constitue un facteur de risque puissant et indépendant de survenue de FA non valvulaire [ 4 ]. La prévalence de la FA dans la population générale est estimée entre 1 et 2% [ 2 , 6 ]. Conformément à ce qui a été trouvé dans notre étude, la prévalence augmente chez les patients présentant certains facteurs de risque tels que l´HTA [ 3 , 7 ].…”
Section: Discussionunclassified
“…L´HTA constitue un facteur de risque puissant et indépendant de survenue de FA non valvulaire [ 4 ]. La prévalence de la FA dans la population générale est estimée entre 1 et 2% [ 2 , 6 ]. Conformément à ce qui a été trouvé dans notre étude, la prévalence augmente chez les patients présentant certains facteurs de risque tels que l´HTA [ 3 , 7 ].…”
Section: Discussionunclassified
“…Isso pode estar relacionado pelo fato de muitos pacientes serem subdiagnosticados quanto à necessidade de utilizarem esses medicamentos, mostrando a importância do registro eletrocardiográfico (Holter) nesses pacientes (Yuyun et al, 2020).…”
Section: Discussionunclassified
“…In Africa, the rate of CA increased gradually following the epidemiological transition of diseases [3]. According to a recent systematic review conducted by Matthew F. Yuyun et al, there are few available health professionals who can adequately manage CA in Africa [4]. In fact, the cardiopulmonary resuscitation awareness for the management of cardiac arrest is generally low and there is scarcity of cardiac implantable electronic devices insertions and invasive arrhythmia treatment centers [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent systematic review conducted by Matthew F. Yuyun et al, there are few available health professionals who can adequately manage CA in Africa [4]. In fact, the cardiopulmonary resuscitation awareness for the management of cardiac arrest is generally low and there is scarcity of cardiac implantable electronic devices insertions and invasive arrhythmia treatment centers [4]. Bonny et al in 2019 identified the low number of trained clinicians who could detect and manage CA [5].…”
Section: Introductionmentioning
confidence: 99%